SCN5A mutation status increases the risk of major arrhythmic events in Asian populations with Brugada syndrome: systematic review and meta‐analysis - Rattanawong, Pattara (Ann Noninvasive Electrocardiol, 2018)
BACKGROUND: Brugada syndrome (BrS) is an inherited arrhythmic disease linked to SCN5A mutations. It is controversial whether SCN5A mutation carriers possess a greater risk of major arrhythmic events (MAE). We examined the association of SCN5A mutations and MAE in BrS patients. METHODS: We comprehensively searched the databases of MEDLINE and EMBASE from inception to September 2017. Included studies were published cohort and case–control studies that compared MAE in BrS patients with and without SCN5A mutations. Data from each study were combined using the random‐effects model. Generic inverse variance method of DerSimonian and Laird was employed to calculate the risk ratios (RR) and 95% confidence intervals (CI). RESULTS: Seven studies from March 2002 to October 2017 were included (1,049 BrS subjects). SCN5A mutations were associated with MAE in Asian populations (RR = 2.03, 95% CI: 1.37–3.00, p = 0.0004, I (2 )= 0.0%), patients who were symptomatic (RR = 2.66, 95% CI: 1.62–4.36, p = 0.0001, I (2 )= 23.0%), and individuals with spontaneous type‐1 Brugada pattern (RR = 1.84, 95% CI: 1.05–3.23, p = 0.03, I (2 )= 0.0%). CONCLUSIONS: SCN5A mutations in BrS increase the risk of MAE in Asian populations, symptomatic BrS patients, and individuals with spontaneous type‐1 Brugada pattern. Our study suggests that SCN5A mutation status should be an important tool for risk assessment in BrS patients.